ATTAMPTED SUICIDE – ITS CAUSES AND EFFECTS - Dwivedi, Shree (International Journal of Research -GRANTHAALAYAH, 2015)
One’s death is not the end, but the beginning for those who are still living. To the untrained eye, suicide may appear to be a highly individual decision, and undoubtedly it is. However, it can be shown that suicide, as with the results of so many other individual choices, is also a socially patterned and socially reactive phenomenon. Since ancient times, suicide has been an object of moral and philosophical speculation; later, it also became a matter for medical and social-scientific thought. Studies on attempted suicides have been conducted by many scientists and social workers in other countries, though very little work seems to have been done in our country on this problem. It is important to bear this distinction in mind, because the present study revealed that the patients concerned did not really want to die; they only utilized their attempts as a threat to express dissatisfaction with certain conditions.